Unplanned Settlements and Its Repercussions on The Urban Environment - The City of Hilla as a Model - Manar Ali Sultan Al-Saeed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The city of Hilla has suffered from the problem of unplanned settlements that spread among the residential neighborhoods because of several reasons. The phenomenon of unplanned settlements has grown. Later became one of the biggest problems that threatening the area of this study because of its negative effects on the city due to mass migrations and the huge problems that accompanied this migrations especially after 2003, including migration from the countryside to the city because of climatic conditions such as drought seasons and low rainfall and forced displacement due to sectarianism, chaos and insecurity in many provinces in Iraq when Babylon received about (11890) people in 2014 in addition to the control of some groups on State lands and the construction of informal dwellings on these lands due to the absence of law and the government pay no attention for these violations which affected the city’s layout and its urban appearance. All these factors led to form a socio-economic fabric that does not fit the inhabitants of the city. The study found that the number of unplanned settlements in the city of Hilla is (4832) housing units and a population of (33824) people in 2013. This number has increased to (14,180) housing units with an area of (829.4 hectares) in 2022. The study also showed a high percentage of unplanned units which is constructed of (block) material than others by (43.9%). The study revealed an increase in the population of unplanned settlements to (99,260) inhabitants. This increasing is a clear indicator of an impact of unplanned settlements on community services. As education was affected by unplanned settlements residents and became outside the planning standards that stipulate that the number of students in all stages should not exceed (25-35) per class. Whereas the number exceeded (55) students per class, subsequently in each school, the number exceeded 450 student. On the health side, the share of one doctor of patients (2700 inhabitants / doctor) per month and this, of course, exceeds the approved standard (1000 inhabitants / doctor) especially the city already suffers from a severe shortage of health institutions. In addition, the per capita share of water in the city has decreased to less than (288 liters / day) with a deficit rate of (15%) from the Iraqi standard (450 liters / day). The waste thrown by the people of the unplanned settlements in the streets was a major problem that leads to many health risks. The process of littering outside the houses came in first place with a percentage of (41.0%), the burning of waste came in second place with a percentage of (31.7%).